Post-sentence supervision: A case study of the extension of community resettlement support for short sentence prisoners - Cracknell, Matthew (Probation journal, 2020)
Introduced under the Transforming Rehabilitation reforms, the Offender Rehabilitation Act 2014 created a period of post-sentence supervision (PSS) after licence for individuals serving short custodial sentences. This empirical study features on the ground views and perspectives of practitioners and service users of PSS in one case-study area. Findings from this research suggest a number of issues and ambiguities with the enactment of the sentence. These include ambiguities regarding the correct use of enforcement procedures; the antagonistic relationship between third sector and Community Rehabilitation Company staff, primarily centred around transferring cases and concerns over the use of ‘light touch’ supervision and uncertainties over what the rehabilitative aims of this sentence mean in practice. These issues led to practitioners questioning the legitimacy of the third sector organisation involved in the management of PSS, while service users experienced PSS as a frustrating ‘pass-the-parcel’ experience, where resettlement support was constantly stalled and restarted at each juncture of the sentence. Before briefly discussing the potential future of PSS under the next iteration of probation policy, this article concludes by arguing that there is emerging evidence of a commonality of failures occurring at every juncture of the short sentence, undermining resettlement prospects for the long-neglected short sentence population.